Utilização digestiva e energia líquida de produtos do beneficiamento do arroz avaliadas com leitões - Schirmann, Graciele Dalise (2016)
In swine production the post weaning period is considered one of the most critical periods of the production. The state of Rio Grande do Sul presents great availability of by-products from rice processing that may be an alternative on the feeding of swine. The net energy is the one that represents better the energy value used by the animal however its determination by the conventional methods results in costs and manpower, being suggested the use of prediction equations for calculating. Two digestibility trials were performed with 12 and 18 male castrated swine with initial weight of 8 kg and 16 kg, respectively. In both studies, the animals were placed in metabolic cages during a period of twelve days, being seven days of adaptation and five days of collection. The experimental procedure was the total fecal collection using the ferric oxide as fecal marker. Data of digestibility and energy values of the co products were submitted to variance analysis using the completely randomly design and the Tukey test, used for comparing the averages between the feed. The digestibility coefficients of the organic matter, crude protein and gross energy were higher (P<0.000) for the broken rice (BR) compared to the stabilized rice bran (SRB) and parboiled rice bran (PRB). On the other hand, the BR presented lower (P<0.000) digestibility coefficient of the mineral matter than the rice bran's evaluated. The PRB presented a digestible energy 2% lower than the BR and 5% higher than the SRB. The observed metabolized energy on BR was the highest, followed by the PRB and SRB that presented the lowest value. The average value of net energy was 3094, 2646 and 2818 kcal/kg for the BR, SRB and PRB, respectively. The net energy value varies according to the equation used to estimate it. Based on data of chemical composition, digestible using and energy values it may be affirmed that the broken rice stabilized rice bran and parboiled rice bran may be used on the feeding of piglets.